The Black Sea Slave Trade in the 13th–14th century That Changed the Political Balance in the Near East - Dashdondog B. (Золотоордынское обозрение)
Objective: Maritime issues tied to the Mongol Empire cover not only Southeast Asia, but also the Black Sea region and the Byzantine Empire’s borders, reaching as far as the Mediterranean Sea. The Black Sea commercial activity attracted the Mongols especially as it relates to a slave trade that subsequently changed the political balance in the Middle and Near East. Materials: In this paper, I aimed to address the relevant region and the slave trade that involved many regional political powers. The primary sources and archival documents of various types reveal that the multiparty relations between the Mongols of the Golden Horde, Byzantium, and Egypt involved the captives that were taken from the Black Sea region and enslaved in the Mediterranean. Results and novelty of research: Unlike the slaves of the late medieval period, the teenage boys sold to Cairo in the 13th–14th century became military experts who achieved a high level of political power in the Near East. This action characterizes not only the dynamism of the region, but also drove the phenomenon that led to the formation of a new statehood in then hands of the slaves known as the Mamluks. In fact, the replacement of a Mongol nomad element by a Qipchaq nomad element in the Middle and Near East was a phenomenon that brought about not only a shift in the hegemony, but also demographic and economic growth in the region.